Innovation in Dental Conservation and Their Impact on Forensic Odontology - Fauziah, Yessy Andriani; Wahjuningrum, Dian Agustin; Darmadi, Eveline Yulia; Adityatama, Anneke Paramita (Conservative Dentistry Journal, 2024)
Background: Innovations in dental conservation are increasingly integral to advancements in forensic odontology. Integrating digital technologies, such as intraoral scanning, CAD/CAM, and 3D printing, has enhanced the precision and efficiency of dental record creation. Purpose: To examine and analyse new technologies and tools in dental conservation which play a crucial role in forensic identification, where accurate dental matching is essential for personal identification. Dental identification systems, including microchips and identification tags on prosthetics, are being implemented to aid in mass disaster victim identification. Reviews: Techniques like virtual dental autopsy offer reliable remote examination capabilities, making them invaluable in emergencies. These technologies facilitate more accurate and durable restorations, enhancing patient outcomes in clinical settings while also providing forensic odontologists with robust tools for human identification, especially under challenging conditions such as mass disasters. This paper explores various innovations in dental conservation and their impact on forensic odontology, emphasizing accuracy, speed, and ethical benefits for human identification processes. Conclusion: The advancements illustrate the transformative impact of digital innovation in dental science, setting new standards in both dental care and forensic applications